Pembinaan Prestasi Cabang Olahraga Bola Voli pada Klub IVOKAB Kabupaten Pekalongan (Indonesian Journal for Physical Education and Sport, 2023)
The management of IVOKAB club pekalongan regency is still less than optimal, due to the lack of human resources (HR) of the board, infrastructure facilities are still minimal, it is due to the lack of budget funds so that it is still less than optimal in the planning of the training program. The purpose of this study is to find out the achievements, nurseries, and coaching achievements of the volleyball sport club IVOKAB Pekalongan Regency in 2021. This type of research is a qualitative naturalistic method. Data collection techniques through observation, interviews, documentation. The 12-person source consisted of 1 manager, 3 coaches and 8 athletes. The study used data and source triangulation to verify the validity of the data. Data analysis techniques used include data reduction, data presentation and verification. The results obtained are as follows: (1) The processing of ivokab clubs has been going well, because of the direct and indirect strategy, to maximize the quality of IVOKAB clubs. (2) IVOKAB club nursery is already going well, because the nursery is done networking through tests and categorized with age-appropriateness. (3) achievement is quite good, because the condition of the club is still new, for the annual event in Pekalongan Regency only regional tournaments only.